2011
DOI: 10.1007/s00442-011-1936-x
|View full text |Cite
|
Sign up to set email alerts
|

Polychaete invader enhances resource utilization in a species-poor system

Abstract: Ecosystem consequences of biodiversity change are often studied from a species loss perspective, while the effects of invasive species on ecosystem functions are rarely quantified. In this experimental study, we used isotope tracers to measure the incorporation and burial of carbon and nitrogen from a simulated spring phytoplankton bloom by communities of one to four species of deposit-feeding macrofauna found in the species-poor Baltic Sea. The recently invading polychaete Marenzelleriaarctia, which has sprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 63 publications
8
46
1
Order By: Relevance
“…In the Baltic, colonization by macrofauna, particularly of the invasive genus Marenzelleria, is expected once normoxia is established (Schiedek 1997, Leppä -koski et al 2002, Karlson et al 2011. Our results indicate a 50% decrease in denitrification and a 3-fold increase of DNRA in sediment inhabited by Marenzelleria compared to normoxic non-bioturbated sediments, resulting in a net stimulation effect of denitrification by bottom water oxygenation of only a factor 3 compared to the HY treatment.…”
Section: Denitrification and Dnra Rates Under Hy No And Nob Conditionssupporting
confidence: 49%
“…In the Baltic, colonization by macrofauna, particularly of the invasive genus Marenzelleria, is expected once normoxia is established (Schiedek 1997, Leppä -koski et al 2002, Karlson et al 2011. Our results indicate a 50% decrease in denitrification and a 3-fold increase of DNRA in sediment inhabited by Marenzelleria compared to normoxic non-bioturbated sediments, resulting in a net stimulation effect of denitrification by bottom water oxygenation of only a factor 3 compared to the HY treatment.…”
Section: Denitrification and Dnra Rates Under Hy No And Nob Conditionssupporting
confidence: 49%
“…For example, the introduction of Marenzelleria spp. may have implications for both the productivity of the system (Karlson et al, 2011) and for sediment nutrient dynamics (Norkko et al, 2012).…”
Section: Implications For Ecosystem Functionmentioning
confidence: 99%
“…Furthermore, in the 1980s and early 1990s the sediment hosted different communities of bioturbating fauna dominated by the amphipods Monoporeia affinis and Pontoporeia femorata (Elmgren and Larsson 1997), whereas today the widespread polychaete Marenzelleria spp. dominates benthic macrofauna (Elmgren and Larsson 1997;Karlson et al 2011). Karlson et al (2005) showed that the bioturbation activity of M. affinis stimulated N 2 removal compared to non-bioturbated sediment, whereas recent experiments with conditioned sediment with and without Marenzelleria spp.…”
Section: N Transformation Pathways In Himmerfjärdenmentioning
confidence: 99%